2018
DOI: 10.15649/2346075x.483
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radon (222Rn) and thoron (220Rn) concentration of plants (Vegetables) in different locations in Sulaimania City using CR-39 detector

Abstract: Introduction: Radon is a radioactive gas released from the normaldecay of uranium in rocks and soil depending on local geology. Radioactive decay of uranium through radium produces radon. Materials and Methods: In the present work, seventeen plant (vegetables) samples collected from Sulaimania Governorate. The plants have been analyzed and examined to measure the level of radon (222Rn) and thoron (220Rn) using plastic track detector (CR-39) for evaluation of radon and thoron concentration in this region. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Radon concentration, activity of radon, specific of radon and effective dose equivalent from each vegetable and fruit samples are showed in tables 1 and 2 Tables 1 and 2 show the results of the radon concentration from each vegetable and fruit samples varied from 6.27 to 45.11 Bq/m 3 with an average of 21.32±2.36 Bq/m 3 and varied from 12.11 to 53.19 Bq/m 3 with an average of 27.47±2.81 Bq/m 3 , successive. The measurement results of radon concentration from each vegetable and fruit sample were less than the action level of 190 Bq/m 3 , as advised by EPA [4]. Calculation of effective dose equivalent from the resultant of the radon concentration was found that valuable from 0.042 to 0.138 µSv/y with an average of 0.03±0.007 µSv/y and Valuable from 0.008 to 0.137 µSv/y with an average of 0.045±0.008 µSv/y, respectively.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Radon concentration, activity of radon, specific of radon and effective dose equivalent from each vegetable and fruit samples are showed in tables 1 and 2 Tables 1 and 2 show the results of the radon concentration from each vegetable and fruit samples varied from 6.27 to 45.11 Bq/m 3 with an average of 21.32±2.36 Bq/m 3 and varied from 12.11 to 53.19 Bq/m 3 with an average of 27.47±2.81 Bq/m 3 , successive. The measurement results of radon concentration from each vegetable and fruit sample were less than the action level of 190 Bq/m 3 , as advised by EPA [4]. Calculation of effective dose equivalent from the resultant of the radon concentration was found that valuable from 0.042 to 0.138 µSv/y with an average of 0.03±0.007 µSv/y and Valuable from 0.008 to 0.137 µSv/y with an average of 0.045±0.008 µSv/y, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…Calculation of effective dose equivalent from the resultant of the radon concentration was found that valuable from 0.042 to 0.138 µSv/y with an average of 0.03±0.007 µSv/y and Valuable from 0.008 to 0.137 µSv/y with an average of 0.045±0.008 µSv/y, respectively. The effective dose equivalent for the consumption of vegetables and fruits in the mentioned locations for people is less than that suggested by EPA is 1.3 mSv/y [4,14].…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations